(untitled) (Politeja, 2025)
CONSTITUTIONALISM IN BURKINA FASO IN THE CONDITIONS OF DESTABILIZATION OF THE POLITICAL SYSTEM AFTER THE RESIGNATION OF PRESIDENT BLAISE COMPAORÉ This article concerns the evolution of Burkina Faso’s constitutionalism with particular emphasis on the period following the fall of Blaise Compaoré’s presidency. The author draws attention to the dynamics of constitutional transformations that occurred as a result of the deteriorating internal situation. The key factor influencing institutional changes was the introduction and consolidation of the transitional regime, which occurred as a result of two coups in 2022. Despite the adoption of a separate constitutional act (transitional period charter), the provisions of the 1991 constitution remain in force (unless they conflict with the provisions of the charter). In this respect, the changes that were taking place did not stand in the way of maintaining the relative constitutional continuity of the state. The same can be said about the rules of the semi-presidential system of government that remained in force, although their application in the new conditions would require the establishment of the rules of a democratic political system.